Mya in the middle - Allen, Crystal (Allen, Crystal. Magnificent Mya Tibbs., 2020)
Nine-year-old Mya doesn't like being the middle child, feeling she's always on the outside. She sees her chance to become a star, though, when she gets the chance to start a school newspaper. But the project also gives her archenemy, Naomi Jackson, a chance to once again put Mya on the outside by proving she's a better friend to the twins Skye and Starr. And when Mya makes a huge mistake, she stands to lose everything.